Hubungan Antara Kontribusi Edukatif Orang Tua Dengan Hasil Belajar Murid Kelas III SD Inpres Jongaya Kota Makassar - Syarifah Nur Fajrin; Syarifah Aeni Rahman (STKIP Andi Matappa Pangkep, 2020)
The main problem in this study is to determine the relationship between the educational contributions of parents and the learning outcomes of grade III students of SD Inpres Jongaya, Makassar City. This study aims to determine the extent of the relationship between the educational contributions of parents and the learning outcomes of class III SD Inpres Jongaya Makassar City. The type of research used is correlational, this study seeks to reveal the relationship between the educational contribution of parents and social studies learning outcomes of students at SD Inpres Jongaya, Makassar City. The subjects in this study were 31 class III students. Data collection techniques in this study used questionnaires, tests and documentation. The data analysis technique used to analyze the research data was inferential descriptive statistical analysis using product moment correlation analysis for hypothesis testing. The results in this study indicate that there is an educational contribution from parents to grade III SD Inpres Jongaya students in the medium category with average learning outcomes. -average 82.3. Based on the results of this study, it can be concluded that there is a significant relationship between Parents' Educational Contribution and Learning Outcomes of Class III students of SD Inpres Jongaya Makassar City.